2007
DOI: 10.1172/jci30910
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of leptin receptor expression in the pancreas directly affects β cell growth and function in mice

Abstract: Obesity is characterized by hyperinsulinemia, hyperleptinemia, and an increase in islet volume. While the mechanisms that hasten the onset of diabetes in obese individuals are not known, it is possible that the adipose-derived hormone leptin plays a role. In addition to its central actions, leptin exerts biological effects by acting in peripheral tissues including the endocrine pancreas. To explore the impact of disrupting leptin signaling in the pancreas on β cell growth and/or function, we created pancreas-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 44 publications
13
182
3
Order By: Relevance
“…The lack of leptin signaling is a likely contributor to this volume expansion. Indeed, using pancreas-specific leptin receptor KO mice, it has been shown that the disruption of leptin action in islets results in enhanced PI3K/AKT signaling, associated with increases in beta cell size and islet mass (17). Although this compensatory islet growth has been demonstrated in vitro, we are now able to verify this pattern in the living ob/ob mouse longitudinally through the analysis of single reporter islets.…”
Section: Intraocular Islet Transplants Mirror the Adaptive Morphologicalmentioning
confidence: 81%
“…The lack of leptin signaling is a likely contributor to this volume expansion. Indeed, using pancreas-specific leptin receptor KO mice, it has been shown that the disruption of leptin action in islets results in enhanced PI3K/AKT signaling, associated with increases in beta cell size and islet mass (17). Although this compensatory islet growth has been demonstrated in vitro, we are now able to verify this pattern in the living ob/ob mouse longitudinally through the analysis of single reporter islets.…”
Section: Intraocular Islet Transplants Mirror the Adaptive Morphologicalmentioning
confidence: 81%
“…Thereby, insulin secretion was decreased (26). Additionally, leptin acted directly on b-cells to block the secretion of insulin (28,29). Of note, by enhancing bone resorption, the active, undercarboxylated form of OC is indirectly released (Fig.…”
Section: Bone Acts As An Endocrine Organmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies have shown that this hormone activates a diversity of events in the b-cell, which will be reviewed in the next sections. Additionally, experiments in knockout (KO) mice with specific deletion of the leptin receptor in the pancreas or in the b-cell and the hypothalamus have shown alterations in glucose homeostasis as well as in b-cell function and mass in these animals (Covey et al 2006, Morioka et al 2007. Leptin signaling defects in b-cells lacking the leptin receptor lead to hyperinsulinemia, which develops prior to insulin resistance (Gray et al 2010).…”
Section: Leptin and Glucose Homeostasismentioning
confidence: 99%
“…Three tyrosine residues, whose phosphorylation is important for leptin signaling, are indicated in ObRb: Y985 interacts with the SH2-containing protein tyrosine phosphatase 2, Y1077 with STAT5, and Y1138 with STAT3. specific disruption of the Obr(Lepr) gene either in the pancreas or in the b-cell and hypothalamus (Covey et al 2006, Morioka et al 2007.…”
Section: Leptin Receptors In the Pancreatic B-cellmentioning
confidence: 99%